PELAKSANAAN PERJANJIAN BAGI HASIL PERUMAHAN TITAN ARUM HOUSE ANTARA PEMILIK TANAH DENGAN PELAKSANA PEMBANGUNAN PT. RUBEK MEUPAYONG (Studi Penelitian di Kabupaten Aceh Barat Daya) - Syahputra, Imam Zirham; Faisal, Faisal; Kurniasari, Tri Widya (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
This study is intended to determine the implementation of the rights and obligations of the parties to the production-sharing contract and the obstacles and efforts to resolve defaults carried out by the executor of the Titan Arum House housing development. The problem of this study is the implementation of the rights and obligations of the parties in the profit-sharing agreement and obstacles as well as efforts to resolve defaults carried out by the executor of the housing development Titan Arum House. The study method is empirical juridical, with descriptive analysis, namely providing an overview and disclosure of the implementation of profit-sharing agreements for housing development in Southwest Aceh District. The agreement was caused by the agreement of the parties with the principle of freedom of contract. The agreement made by the parties is carried out by putting it in the form of a written agreement made before an authorized notary. The parties agreed to build 25 housing units on the land of the first party for 8 months. The second party carried out the construction for 11 months, so it was considered a default not in accordance with the specified time. The default was due to obstacles in the form of inaccuracy in analyzing time and Budget Details (RAB). The settlement efforts taken by both parties are by way of deliberation in order to obtain a mutually beneficial agreement. The two sides again made an addendum containing an additional three months of construction time.